Analisis Tingkat Profitabilitas Sebelum dan Selama Pandemi COVID-19: (Studi Kasus Pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia) - Meriantini, I Gusti Agung; Yasa, I Nyoman Putra (Jurnal Pendidikan Ekonomi Undiksha, 2023)
The economy in Indonesia is experiencing a slump due to the COVID-19 pandemic. The problems caused by the COVID-19 pandemic in the real sector or the business world have the potential to cause problems in the banking sector. Banks in Indonesia still rely a lot on their operating income from lending. With the current economic conditions, it is feared that there will be many bad loans, and this will affect the level of profitability. This study aims to analyze the level of profitability before and during the covid-19 pandemic (case study on banks listed on the Indonesia Stock Exchange). The research method used is a quantitative method with the object of research being the financial data of banking companies listed on the IDX. The sampling technique used in this research is the purposive sampling method, and the data collection method used is the documentation method. The data analysis technique used the paired sample t-test, which was processed with SPSS 22 for Windows. The study uses financial data for the 2019-2020 period. The results showed that there was a significant difference in ROA between before and during the COVID-19 pandemic with a significance value of 0.00. While ROE and NPM there are no significant differences between before and during the COVID-19 pandemic in banking companies listed on the IDX.